Multi‐sample measurement of hyperpolarized pyruvate‐to‐lactate flux in melanoma cells. (12th December 2020) - Lees, Hannah; Millan, Micaela; Ahamed, Fayyaz; Eskandari, Roozbeh; Granlund, Kristin L.; Jeong, Sangmoo; Keshari, Kayvan R.
Abstract : Hyperpolarized [1‐ 13 C] pyruvate can be used to examine the metabolic state of cancer cells, highlighting a key metabolic characteristic of cancer: the upregulated metabolic flux to lactate, even in the presence of oxygen (Warburg effect). Thus, the rate constant of 13 C exchange of pyruvate to lactate, k PL, can serve as a metabolic biomarker of cancer presence, aggressiveness and therapy response. Established in vitro hyperpolarized experiments dissolve the probe for each cell sample independently, an inefficient process that consumes excessive time and resources. Expanding on our previous development of a microcoil with greatly increased detection sensitivity (10 3 ‐fold) compared with traditional in vitro methods, we present a novel microcoil equipped with a 10‐μL vertical reservoir and an experimental protocol utilizing deuterated dissolution buffer to measure metabolic flux in multiple mass‐limited cell suspension samples using a single dissolution. This method increases efficiency and potentially reduces the methodological variability associated with hyperpolarized experiments. This technique was used to measure pyruvate‐to‐lactate flux in melanoma cells to assess BRAF‐inhibition treatment response. There was a significant reduction of k PL in BRAF V600E cells following 24 and 48 hours of treatment with 2 μM vemurafenib ( P ≤ .05). This agrees with significant changes observed in the pool sizes of extracellular lactate ( P ≤ .05) and glucose ( P ≤ .001) following 6 and 48 hours of treatment, respectively, and a significant reduction in cell proliferation following 72 hours of treatment ( P ≤ .01). BRAF inhibition had no significant effect on the metabolic flux of BRAF WT cells. These data demonstrate a 6‐8–fold increase in efficiency for the measurement of k PL in cell suspension samples compared with traditional hyperpolarized in vitro methods. Abstract : We present a novel system and experimental protocol, using a hyperpolarized micromagnetic resonance spectrometer, to allow for the real‐time measurement of metabolic flux in multiple mass‐limited cell suspension samples in a single hyperpolarized dissolution. This technique was applied to measure the rate of conversion of hyperpolarized [1‐ 13 C] pyruvate to [1‐ 13 C] lactate, k PL, in melanoma cells for the assessment of BRAF inhibition treatment response. We detected significantly reduced k PL in BRAF V600E cells following 24‐ and 48‐hour treatments with 2 μM vemurafenib.